Double Chamber Type Seawall Performance For Reducing Long Sea Waves And Extracting Energy - Husain, Firman (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
Coastal damage caused by sea wave attack has increased significantly recently. This will have an impact on the loss of residence and economic resources of coastal communities. In some incidents it has even claimed lives. Therefore, it is necessary to build a sea wall that can withstand the attack of sea waves both for short wave types and for long sea wave types which are usually provoked by storm winds. In this study a seawall type with double chambers was tested. From the test results it can be seen that this type of seawall is effective in being able to withstand attacks by sea waves both short and long seas because of the existence of double spaces that can expand the range of wave frequencies so that wave height can be reduced constructionally. In this study it has also been confirmed that the wave amplification value is around 2.5 times the incident wave height, which means that the wave energy in the seawall chamber can be utilized. -spasi-Times New Roman 11 Italic- Keyword: Beaches, Waves, Seawalls and Wave Amplification